2015
DOI: 10.1007/s11010-014-2315-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of SOX4 is a biomarker for malignant status and poor prognosis in patients with non-small cell lung cancer

Abstract: The aim of the present study was to analyze the expression of sex-determining region Y-related high mobility group box 4 (SOX4) in non-small cell lung cancer (NSCLC) and its correlation with clinicopathologic characteristics, including the survival of NSCLC patients. To observe initially the expression status of SOX4 in lung squamous cell carcinoma and adenocarcinoma at gene expression omnibus. The expression of SOX4 mRNA and protein was examined in NSCLC tissues and normal lung tissues through real-time PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…Abnormal overexpression of SOX4 has been observed in various human cancers, including prostate cancer (32), breast cancer (33) and esophageal squamous cell carcinoma (34). Additionally, Wang et al (35) reported that increased expression of SOX4 is a biomarker for malignant status and poor prognosis in patients with non-small cell lung cancer. Hur et al (36) showed that SOX4 overexpression regulates the p53-mediated apoptosis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal overexpression of SOX4 has been observed in various human cancers, including prostate cancer (32), breast cancer (33) and esophageal squamous cell carcinoma (34). Additionally, Wang et al (35) reported that increased expression of SOX4 is a biomarker for malignant status and poor prognosis in patients with non-small cell lung cancer. Hur et al (36) showed that SOX4 overexpression regulates the p53-mediated apoptosis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SOX4 has been observed to be overexpressed in a variety of cancers, such as breast cancer, non‐small cell lung cancer, ovarian cancer, endometrial cancer, bladder carcinoma and prostate adenocarcinoma, although decreased expression has been occasionally reported (such as in melanoma and gallbladder cancer) . SOX4 overexpression is associated with advanced stage in breast cancer, poor prognosis in prostate adenocarcinoma and non‐small cell lung cancer, and tumor progression in hepatocellular carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…SOX4 is overexpressed in multiple types of human cancer, including gastric cancer (43), hepatocellular carcinoma (44), prostate cancer (45), osteosarcoma (46) and non-small cell lung cancer (47). Furthermore, multiple studies have demonstrated that SOX4 serves an oncogenic function in tumorigenesis and tumor development.…”
Section: Discussionmentioning
confidence: 99%